Analisis Penerimaan Pajak Reklame Guna Meningkatkan Pendapatan Asli Daerah (Studi Kasus Badan Pendapatan Daerah Kota Medan) - Pohan, Raihan Adha Rahman; Aslami, Nuri (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The research conducted at the Regional Tax and Retribution Management Agency of Medan City aims to identify and analyze the realization value of advertising tax revenue with the goal of enhancing Local Own-Source Revenue (PAD). The research focuses on reasons behind achieving the advertising tax revenue target, low compliance, and the impact of new regulations imposing burdens on advertising entrepreneurs. The research employs a descriptive approach, analyzes survey data from 2020 to 2022, and compares findings with relevant theories. The study reveals an increased contribution to advertising tax revenue, attributed to factors such as suboptimal enforcement and supervision, low awareness among advertising entrepreneurs, and issues with sub optimal tax reporting.